Sejarah Pemikiran Ekonomi Islam - Rusdin Muhalling (Al-'Adl, 2009)
Along with spirit of returning to Al-Qur’an and of sunnah, and assured by disappointment at economic system performance result that embraced, don’t know socialism and or capitalism, hence since two a decay lately, reappear, relatively intensively economic system discourse of Islam. Apparition return this discourse have generated a various reaction, good among Moslem people, and non Moslem, isn’t it to three group, different in staring at the economic system of Islam. First, they who is to see that economic system of Islam is the same with capitalism system meagrely change. Both/ second, they who tell that there is an important difference among/between the conventional system (Capitalism and socialism) and Islam economics, but this evidence that Islam teaching does not transformation become a consistent economic system of function in his structure. Third, they who have a notion that economic system of Islam doesn’t have an erudite base. On the basis of that, so that all Islam economics develop; build a model to prove the existence and at the same time place position relative economic system of Islam to economic system of capitalism and socialism, with confidence that economic system of that Islam it is true to exist, in all economic sector and level.